Keseimbangan Jiwa, Psikopatologi, dan Tindakan Perawatan Perspektif Zakariya Ar-Razi - Sa'adah, Nayla Afna; Soleh, Achmad Khudori (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2025)
In the midst of the hustle and bustle of a stressful life, mental balance, which is built from wise reasoning, managed emotions, and controlled self-drive, is an important key in maintaining mental health. This research aims to understand how Zakariya Ar-Razi views the importance of mental balance in maintaining mental health, explain the concept of psychopathology, and explore various treatment approaches that have been developed as an effort to restore body and soul. This research uses a qualitative method with a literature study approach, exploring literature in books and previous research containing the psychological thoughts of the character Zakariya ar-Razi. The results of this research show that: 1) Mental balance according to Zakariya ar-Razi is achieved through harmony between the three elements of the soul, namely rational, emotional and vegetative, with the active role of reason in directing and controlling emotions to create psychological stability and moral behavior. 2) In psychopathology, mental disorders according to Zakariya ar-Razi are rooted in an imbalance between reason and emotion, which is triggered by the dominance of desires and inner drives, so they require psychological and rational treatment, not just medical. 3) The treatment approach developed by ar-Razi is comprehensive, integrating humanistic therapy, clinical and spiritual aspects, emphasizing the importance of self-introspection and managing desires as the main factors in the healing process of body and soul (caused by desires and tabi'at).